Building Compliant Entrepreneurs: A Field Experiment on Tax Training and Business Outcomes - Rahmat Saputra, Widi; Qurrota A'yun, Annisa (Journal Economic Business Innovation, 2025)
Purpose: The purpose of this study is to find out the influence of tax training program on tax compliance, tax filing timeliness, tax reporting accuracy, and business performance of beginner entrepreneurs in Indonesia.Methods: A field experiment was implemented with new entrepreneurs randomized into tax training and no tax training groups. Data was gathered from surveys and business performance metrics, and statistical analysis was used to test the hypotheses.Results: Entrepreneurs receiving tax training had a significant increase in their tax compliance; they filed in a timely manner, reported taxes with greater accuracy and completeness, and had better business performance than entrepreneurs not receiving training.Novelty: This study adds to the understanding of the impact of tax education on entrepreneurial behavior in the context of tax compliance, which is vital for emerging economies such as Indonesia.Implications: These findings have a significant implication not just for tax policy but also for entrepreneurship, as they demonstrate that tax training can enable novice entrepreneurs to efficiently manage their tax obligations and, by extension, succeed in their businesses. To begin with, we call on policymakers to support broad-based tax education programs to encourage a culture of compliance and business success.